Contribution to the improvement of pharmacy services at attendance of patients with STD complants in Campo Grande - MS - Ajalla, Maria Elizabeth; Castro, Lia L.C de (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Sexually Transmitted Diseases (STDs) have constituted a long-time Public Health issue. his problem became more evident with the appcarance of aids, as resistance contributes to maintaining the incidence leveis of this disease. lt is widely known that thc Brazilian population seeks care for their health problems directly from pharmacy countcrs, rather than from more adequate health care providers. Several investigators have already reported such prescriptionless drug dispensation pattern, both illegal and irrational, practiced in pharmacies throughout the country. The present work was aimed at contributing to the improvement of pharmacy services in the municipaliry of Campo Grande, Mato Grosso do Sul state, Brazil. The universe of study was composed of ali the pharmacies officially listed in the records of the Regional Council of Pharmacy of Mato Grosso do Sul (CRF/MS) at the time of this research. The first stage of the study investigated the professional practice of pharmacy workers when serving a patient who described having gonorrhea symptoms. The second stage consisted in training those phannacists who held technical responsibility for the establishments so that they would develop an instructional manual containing guiderines for the professional training of their salespcrsons. The latter were also offered a basic course on STDs. Four months later the results of these interventions were evaluated. Another, large-scale educational intervention addressed to pharmacists. independently provided by thc Federal Council of Pharmacy, was simultaneously evaluated 92.5% of the pharmacies listed at CRF/MS took part in our study, and ali of these provided responses, which revealed a high rate of prescriptionless suggestion of drugs to patients with STD complaints (72% for males. and 62.5% for femalcs). The educational interventions, however. did not significantly alter the panem of drugs being sold withour medical prescription. ln contrast, the educational information provided did alter the behavior of rhose phannacists who owned the phannacies. as did it improve the quality of recommendations provided by lay workers.